COMPREHEND THE THEORY AND CONCEPT OF ENTREPRENEUR COMPETENCY - Wahyudi Henky Soeparto (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
Entering the 21st century, there are many major changes in business practices for both the pioneering scale and the scale of its development. Entrepreneurs are thinking hard in creating competitive advantage. Various kinds of management technologies and concepts that already available have been already applied to their business. So far, although they have applied intensely and massively, it hasn’t shown on the performance of their business. The concept of